2002
DOI: 10.1007/s001980200103
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET Findings of Vertebral Compression Fractures in Osteoporosis: Preliminary Results

Abstract: The aim of this study was to evaluate FDG-PET findings in patients with osteoporosis or preclinical osteoporosis and acute vertebral compression fractures in order to determine whether FDG-PET has a value for distinction of pathological from osteoporotic vertebral fractures. 17 patients with a spontaneous compression fracture of the spine were evaluated by bone scanning with Tc-99m HDP, positron emission tomography with fluorine-18 deoxyglucose (FDG-PET) and magnetic resonance imaging (MRI). Osteoporosis had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(36 citation statements)
references
References 12 publications
0
34
0
2
Order By: Relevance
“…and based on medullary uptake, which is characteristic for malignant fractures (29,30). Fractures in two of our patients were caused by benign lesions, one was PET positive (SUV max.…”
Section: Discussionmentioning
confidence: 76%
“…and based on medullary uptake, which is characteristic for malignant fractures (29,30). Fractures in two of our patients were caused by benign lesions, one was PET positive (SUV max.…”
Section: Discussionmentioning
confidence: 76%
“…• Suspected spinal infection (spondylodiskitis or vertebral osteomyelitis, nonpostoperative) (24)(25)(26)(27)(28). • Evaluation of fever of unknown origin (FUO) (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), including true FUO (defined according to the criteria of Durack and Street (44)), postoperative fever and recurrent sepsis, immunodeficiency (both induced and acquired)-related FUO, neutropenic fever, and isolated acute-phase inflammation markers (persistently raised C-reactive protein and/or erythrocyte sedimentation rate).…”
Section: Common Clinical Indicationsmentioning
confidence: 99%
“…Therefore, SUV in this field should be used with caution in clinical practice. In a single study, though, in spondylodiskitis, an SUV cutoff greater than 3 has been suggested to avoid false-positive findings (26). This criterion, however, cannot be applied for other diseases.…”
Section: Quantitative Analysis (Suv)mentioning
confidence: 99%
“…Radiography, CT, MRI and bone scintigraphy may be nonspecific. Some reports suggest that 18F-FDG-PET may be useful in differentiating between malignant and benign fractures (88)(89)(90)(91), although there are only a few case reports regarding the clinical efficacy of fusion PET/CT on differentiating malignant from benign fractures (92)(93). Overlap of benign and malignant lesions has been shown (94).…”
Section: Differential Diagnosis Of Spinal Tumor By Petmentioning
confidence: 99%